POLA DAKWAH NAHDLATUL ULAMA DI KOTA BANJARMASIN - Fahmi Fahmi (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2015)
Nahdlatul Ulama (NU) is a big organization in Indonesia and it spreads to the entire areas in Indonesia from Aceh to Papua. In central area of Indonesia, precisely in Banjarmasin, NU can exists and recruits a lot of followers who are generally Pesantren-graduates, which are called "Nahdliyyin". This paper employed a science of da'wah approach with a focus on "NU's pattern of da'wah in Banjarmasin", which includes verbal, action, and written models of preaching (da'wah bil lisan, bil hal wa bil kitab). This showed that NU tends to use verbal and action model of da'wah rather than the written one, such as magazine, newspaper, and so on. This differs from other Islamic organizations such as Muhammadiyah and Al-Irsyad in Banjarmasin. However, the contribution of NU in developing and spreading da'wah and NU's mission is significant despite the fact that it is carried out personally and not on behalf of the organization to which the community can look and recognize it as NU's Islamic preaching.